المنظور الشرعي والتكييف القانوني للجريمة الإرهابية. دراسة مقارنة (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Study Dealt With The General Meaning Of The Terrorist Crimes In The Perspective Of Islamic Criminal Legislation By Following The Term Of Terrorism And Its Derivatives In The Holy Qur'an And The Sunnah Of The Islamic Propagation, As Well As The Classification Of Terrorist Crimes And Their Comparison With The Crimes And Conditions Stipulated In The Holy Qur'an And Islamic Criminal Jurisprudence.     The Article Also Dealt With Terrorist Crimes, Both In Terms Of Classification And In The Laws And Regulations Of The Arab And Western Situation, As Well As The Various Criminal Texts Criminalizing The Terrorist Act, As Well As Images And Forms Of Modern Terrorist Crimes Such As Murder, Assassination, Bombings And Hijacking.Hence, The Study Focused On Comparing Terrorist Crimes In Terms Of Their Meaning, Images And Texts In Islamic Criminal Legislation, Especially The Concept Of Barbarism And What Is Identical With And Different From Terrorist Crimes, And The Algerian Penal Code, In Particular The Various Statutes, Key Words- Islamic Perspective - Legal Adaptation-  Terrorist Crime - Comparative